2008
DOI: 10.1093/chemse/bjn022
|View full text |Cite
|
Sign up to set email alerts
|

Synergy and Masking in Odor Mixtures: An Electrophysiological Study of Orthonasal vs. Retronasal Perception

Abstract: Perceptual interactions in a model of wine woody-fruity binary mixtures were previously reported in a psychophysical study performed through orthonasal stimulation only. However, recent studies suggested that the perception of food-like and nonfood-like odors may depend on the route of stimulation. The aim of the present study was two-fold: first to examine the neural correlates of perceptual interactions using electroencephalogram (EEG)-derived event-related potentials (ERPs) and second to test the influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 23 publications
2
30
0
Order By: Relevance
“…Orthonasally, the odor of a drink is perceived as stronger when a colorant is added (Zellner & Kautz, 1990), whereas retronasally the color reduces the perceived intensity (Koza, Cilmi, Dolese, & Zellner, 2005;Zellner & Durlach, 2003). Perceptual differences between the two routes were demonstrated by Heilmann and Hummel for single odorants (Heilmann & Hummel, 2004), and by Ishii and colleagues for odor mixtures (Ishii et al, 2008). On the neural level, Small, Gerber, Mak, and Hummel (2005), showed that different brain areas were recruited according to the stimulation route.…”
Section: Discussionmentioning
confidence: 99%
“…Orthonasally, the odor of a drink is perceived as stronger when a colorant is added (Zellner & Kautz, 1990), whereas retronasally the color reduces the perceived intensity (Koza, Cilmi, Dolese, & Zellner, 2005;Zellner & Durlach, 2003). Perceptual differences between the two routes were demonstrated by Heilmann and Hummel for single odorants (Heilmann & Hummel, 2004), and by Ishii and colleagues for odor mixtures (Ishii et al, 2008). On the neural level, Small, Gerber, Mak, and Hummel (2005), showed that different brain areas were recruited according to the stimulation route.…”
Section: Discussionmentioning
confidence: 99%
“…Münch et al (2013) observed hypoadditivity between odorants on a particular receptor site in flies, due to competitive interactions between the ligands that bind to the same recognition site. Synergy between fruity odorants was observed (Ishii et al, 2008) as well as between additives in meat (Aliani et al, 2013).…”
Section: Factors Influencing Sensory Perception Influence Of Stimulusmentioning
confidence: 94%
“…Direct measurements of brain activity have demonstrated that the two stimulation routes recruit different central pathways. Orthonasal and retronasal presentations of the same odorants evoked cortical event-related potentials with different amplitudes and latencies [2,9,10], and activated different brain areas visualized by functional magnetic resonance imaging [2,11,12]. …”
Section: Introductionmentioning
confidence: 99%